Non-Thermal Liver Ablation: Existing and New Technology - Nakla, Tiffany; Chow, Jacqueline J.; Pham, Kathleen; Abi-Jaoudeh, Nadine (Seminars in Interventional Radiology, 2023)
Cancer has and continues to be a complex health crisis plaguing millions around the world. Alcohol ablation was one of the initial methods used for the treatment of liver lesions. It was surpassed by thermal ablation which has played a big role in the therapeutic arsenal for primary and metastatic liver tumors. However, thermal ablation has several shortcomings and limitations that prompted the development of alternative technologies including electroporation and histotripsy. Percutaneous alcohol injection in the liver lesion leads to dehydration and coagulative necrosis. This technology is limited to the lesion with relative sparing of the surrounding tissue, making it safe to use adjacent to sensitive structures. Electroporation utilizes short high-voltage pulses to permeabilize the cell membrane and can result in cell death dependent on the threshold reached. It can effectively target the tumor margins and has lower damage rates to surrounding structures due to the short pulse duration. Histotripsy is a novel technology, and although the first human trial was just completed, its results are encouraging, given the sharp demarcation of the targeted tissue, lack of thermal damage, and potential for immunomodulation of the tumor microenvironment. Herein, we discuss these techniques, their uses, and overall clinical benefit.
Keywords: liver cancer; ablation; electroporation; histotripsy; interventional radiology; percutaneous alcohol ablation